2021
DOI: 10.3390/ijerph18126580
|View full text |Cite
|
Sign up to set email alerts
|

Combining Kangaroo Care and Live-Performed Music Therapy: Effects on Physiological Stability and Neurological Functioning in Extremely and Very Preterm Infants

Abstract: Interventions such as kangaroo care (KC) and live-performed music therapy (LPMT), are increasingly used to facilitate stress reduction in neonates. This study aims to investigate the effect of combining the two on physiological responses and neurological functioning in very preterm infants. Infants received six sessions of LPMT. KC was added to one LPMT session. Physiological responses included heart rate, respiratory rate and oxygen saturation. We videotaped infants for 30 min before and after two sessions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 50 publications
1
16
0
6
Order By: Relevance
“…Only a few studies compared the effect of kangaroo care or physical contact with and without music therapy [ 20 ], and music therapy with and without kangaroo care [ 21 ], on preterm infants’ vital signs. Combining music therapy with kangaroo care showed stronger declines of heart and respiratory rates and an increase of oxygen saturation compared to kangaroo care alone [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few studies compared the effect of kangaroo care or physical contact with and without music therapy [ 20 ], and music therapy with and without kangaroo care [ 21 ], on preterm infants’ vital signs. Combining music therapy with kangaroo care showed stronger declines of heart and respiratory rates and an increase of oxygen saturation compared to kangaroo care alone [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combining music therapy with kangaroo care showed stronger declines of heart and respiratory rates and an increase of oxygen saturation compared to kangaroo care alone [ 21 ]. Another study with music therapy by a qualified music therapist who sang and played improvised melodies on an ocean disc and guitar showed decreased heart rates and increased oxygen saturations in infants who received music therapy during kangaroo care, while infants receiving music therapy alone showed no vital sign responses [ 20 ]. Matching the results of these two studies, combining kangaroo care and lullaby music showed stronger effects on heart rate and oxygen saturation compared to an only-lullaby music group and a control group receiving kangaroo care [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that music therapy without the voice has the same impact on the patient´s vital signs as other methods of MT, such as lullabies, conversations between parents and children, live music and the combination of other methods that stimulate the connection between parents and neonates. Among the methods of MT explored in other studies, it has been demonstrated that principally the HR shows changes under this adjuvant therapy [6,15,[18][19][20]. It is therefore understood that MT is an alternative therapy with signi cant results and that has the ability to bene t patients in the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…Literatür incelendiğinde, KB sırasında müzik uygulaması sadece KB uygulaması ile karşılaştırıldığı [19][20][21]24,25 , KB sırasında müzik uygulamasının standart bakım ile karşılaştırıldığı 26,27 , KB sırasında müzik uygulamasının sadece müzik uygulaması ile karşılaştırıldığı görülmektedir. 27,28 Meta-analizler kanıt düzeyi yüksek çalışmalardır. İyi tasarlanan bir meta-analiz ile tüm literatürün gözden geçirilmesi mümkündür.…”
unclassified